A novel chronic cirrhosis TAA-induced model in rats - Guerra, Ricardo R.; Trotta, Maurício R.; Aloia, Thiago P. A.; Dagli, Maria L. Z.; Hernandez-Blazquez, Francisco J. (Brazilian Journal of Veterinary Pathology, 2010)
Experimental models for hepatic lesions are necessary so the effectiveness of new drugs in reversing cirrhosis or fibrosis can be tested. This is the case of liver cirrhosis, which requires animal models. Three drugs widely used to induce cirrhosis in animal models are carbon tetrachloride (CCI4), Dimethylnitrosamine (DMN), and Thioacetamide (TAA). TAA has been largely used, but a model that confirms the occurrence of chronic cirrhosis in rats has not yet been well defined. In this study we developed a model of chronic cirrhosis induced by TAA in rats. Our cirrhotic protocol used 200 mg of TAA in 4% aqueous solution per kg of body weight applied intraperitoneally three times per week for 14 weeks in Wistar rats. On the seventh week the dose was increased by 20%. Our protocol caused low mortality rate and represents an alternative and valid model for chronic cirrhosis.